Relationship Nutritional Status and Pulmonary Tuberculosis: Literature Review - Wijayanto, Taufik; Solikhah, Solikhah; Sulistyawati, Sulistyawati (Universitas Ahmad Dahlan, 2024)
Background: The incidence of tuberculosis is an important problem now. One of the risk factors that influence tuberculosis is nutritional status. Malnutrition and tuberculosis are interrelated problems. Aims of the study is to clearly understand the relationship between nutritional status and the incidence of pulmonary tuberculosis literature. Method: A literature review was carried out by searching articles through electronic databases (Google Scholar, PubMed, ScienceDirect, and SpringerLink) using the keywords nutritional status, tuberculosis, risk factors for the incidence of tuberculosis, and nutritional status incidence of pulmonary tuberculosis. The inclusion criteria for the articles used were articles published in accredited National and International publications articles, year of publication of the articles in the range 2017-20123, full text, open access, and cross-sectional study research design. Seven articles were selected for analysis. Articles were analyzed following Prisma Guidelines. Results: Based on a literature review, it was found that there was a relationship between nutritional status and the incidence of pulmonary tuberculosis. Nutritional status affects a person’s immune system. When nutritional status is in poor condition, the body’s immune system will be low, making it susceptible to disease, one of which is pulmonary tuberculosis. On the other hand, tuberculosis can worsen a person’s nutrition due to the disease process. Conclusion: Based on studies, it is explained that nutritional status has a significant relationship and a high risk of the incidence of pulmonary tuberculosis. Nutritional status and pulmonary tuberculosis have a reciprocal relationship.